THE IMPACT OF SOCIAL ISOLATION (COVID-19) ON THE PHYSICAL ACTIVITY INDEX OF STUDENTS AT ESCOLA FRANCISCANA IMACULADA CONCEIÇÃO - DOURADOS-MS (2020-2021) - Sauda, Douglas Rodrigues; Amaro, Eliane Maria (Horizontes - Revista de Educação, 2025)
This article seeks to identify the social isolation impact caused by the pandemic (COVID-19) in the 6th to 9th elementary school students' physical activities index of Franciscana Imaculada Conceição school from Dourados-MS. The new routines imposed by the pandemic were impacted in the families increasing the digital means of communication time, cellphones and computers, and decreasing the physical activities time, lowering the production of the irisin hormone that is released during physical activities action. In 2021, during Physical Education classes, questionnaire e graphics formulations it was possible to identify the level of physical activities presented by the students, due to the social isolation for over one year imposed on the students. The school needed to dynamize the promotion of physical activities aiming to combat the rise of the sedentary lifestyle among teenagers, prepare them to the post pandemic moment with the lowest damage possible and to support the social emotional abilities development through dialogue, reception and life care.